Pengaruh Metode Kasa Steril terhadap Lamanya Pelepasan Tali Pusat pada Bayi Baru Lahir di Wilayah Kerja Puskesmas Alai - Dewi Risnawati; Komaria Susanti; Ary Oktora Sri R; Wira Ekdeni Aifa (Jurnal Siti Rufaidah, 2026)
Umbilical cord infection is one of the leading causes of neonatal mortality in Indonesia. Appropriate umbilical cord care is essential to accelerate separation and prevent infection. In the working area of UPT Puskesmas Alai, variations in cord care practices and delayed separation cases were still found. This study aimed to analyze the effect of umbilical cord care using sterile gauze method on cord separation duration at UPT Puskesmas Alai. The study employed quasi-experimental design with one-group pre-test post-test approach on 32 respondents selected through purposive sampling. Pretest data were obtained from medical records, while posttest data through direct observation. Analysis used Wilcoxon Signed Rank Test (α=0.05). Results showed mean cord separation time in pretest group was 9.2 days (SD=1.08) and posttest group 6.0 days (SD=0.84). Wilcoxon test showed Z=-4.94 with p-value=0.000, indicating significant difference. Umbilical cord care using sterile gauze method effectively accelerates separation time compared to conventional methods. Healthcare workers are recommended to implement this method as standard care.